Influence of sheep grazing on soil chemical properties and growth of rubber (Hevea brasiliensis) in Malaysia - Jusoff, Kamaruzaman (Springer, 1988)
In a rubber estate in Kelantan, Malaysia, sheep grazing increased N, P, Ca and Mg levels and soil pH. Foliar N, P, Ca, Mg and Na also increased with grazing, but K decreased. The girth of rubber trees under grazing had a higher increment than in the ungrazed areas.